Produção de Biogás e Biofertilizante a partir da Digestão Anaeróbia de Cama de Frango - Silva, Wanderson Gomes da (Universidade Federal do Tocantins, 2019)
The objective of this work is to characterize and quantify the biogas production from poultry litter (Napier grass) as a substrate of the anaerobic digestion process for the generation and use of energy. The study was carried out in a biogas plant, in real scale, located at Bom Tempo Farm (Tocantins). The biogas plant uses four substrate feed tanks, followed by four anaerobic reactors (with their respective gas meters) and a stabilization pond, used to receive effluents from all anaerobic reactors. The system has a generator set, responsible for the "burning" of biogas and the production of electric energy. Poultry litter was analyzed for the chemical determination of its main constituents. During the monitoring of the plant under study, samples were collected at the entrance and exit of the system in order to verify the efficiency of removal of organic matter in the biodigester and the chemical characteristics of the biofertilizer produced. Biogas collection was carried out directly in the reactor gasometer at ambient temperatures (23, 28 and 34 oC). Biogas production and consumption of the entire system were monitored on the motor-generator panel. The temperature profile of the exhaust gases was determined during the combustion of the biogas. The results of N, P, K in the biofertilizer samples were, respectively, 45, 33 and 88 g / kg. The values of CH4 and CO2 concentrations in the biogas were, respectively, 52.5 and 47.5%. A positive correlation was observed between the internal temperature of the biodigester and the methane concentration in the biogas. The highest energy production occurred in September (9280 kWh / month), and in February the system produced the lowest amount of energy in the period studied (4064 kWh / month). In the months of July and September, the highest values of energy demand in the farm were observed (around 2000 kWh / month), with extractors and fans being the main responsible for energy consumption (48% of the total). During biogas burning, the engine-generator releases gases with temperatures above 400 oC. The recovery of the thermal energy of the exhaust gas represents another alternative for the generation of energy in the farm studied. The research addressed a correct way for the use of poultry manure, aiming the generation of bioenergy. The technology employed in this scientific research can contribute to a decrease in the cost of electric power of rural properties, providing the economic development and the improvement of the local energy sector.